PENGARUH STORYTELLING TERHADAP PERILAKU EMPATI ANAK - Ayuni, Rita Diah; Siswati, S; Rusmawati, Diana (Jurnal Psikologi, 2013)
Social relationship with others is important when the child enters middle childhood. Empathy behavior is the individual act to put herself or himself in others' feel. Empathy is influenced by individual perspective, gender, intelligence, similarity, experience, innate, discipline methods, and bonding. Through storytelling, children are expected to understand the differences of thoughts and feelings between them and others. This study aims to determine the effect of storytelling on the empathy behavior in the second grade students. A 35 students of Hj. Isriati Baiturrahman 1 elementary school Semarang which selected using nonrandomized pretest-posttest control group design. Measurements were made in lego game setting with 3-4 children per group. The data is collected using observation checklist that consists of 15 behavior indicators and conducted by two observers. The observation supported by audio-video recordings. Independent Sample t-Test and Paired Sample t-Test is used to analyzed the data. The result showed that was not difference between experiment group and control group in empathy behavior. On another hand, used aspect analysis, found that there was difference in fantasy between two groups.Keywords: Children’s empathy behavior, storytelling